Completeness of Descriptions of Repetitive Transcranial Magnetic Stimulation Intervention: A Systematic Review of Randomized Controlled Trials of rTMS in Depression. Issue 1 (March 2019) - Chantebel, Romain; Chesneau, Adélise; Tavernier, Elsa; El-Hage, Wissam; Caille, Agnès
Abstract : Objectives: Repetitive transcranial magnetic stimulation (rTMS) is an innovative therapeutic option in major depressive disorder (MDD). A complete description of the procedure in reports of randomized controlled trials (RCTs) is a prerequisite for implementation of rTMS in clinical practice. The aim of this study was to evaluate the completeness of descriptions of the intervention in RCTs assessing rTMS in MDD. Methods: We performed a systematic review of RCTs evaluating rTMS in MDD and published until August 2016. We searched PubMed, the Cochrane library, and PsycINFO to identify eligible trials. The completeness of the intervention description was evaluated by the use of an adapted-to-rTMS version of the Template for Intervention Description and Replication (TIDieR) checklist. We defined core items that are the most essential to be reported. Missing information was then sought from additional sources and by e-mailing authors. Results: We identified 98 trials reporting 134 interventions. None of the interventions were completely described in the full text of the articles, even after searching additional sources. After contacting the authors, 14 (10.4%) of 134 interventions were completely described. The core items were completely described in 74 (55.2%) of 134 interventions after contacting the authors. Conclusions: We found that rTMS interventions delivered in RCTs are incompletely reported, which prevents their adequate implementation in clinical practice and accurate interpretation of their efficacy. We encourage authors, editors, and reviewers to use the existing reporting guidelines and specifically the TIDieR checklist when describing the intervention. We provide an adapted-to-rTMS TIDieR checklist that could help in the reporting of future trials. Abstract : Supplemental digital content is available in the text.